2010
DOI: 10.1177/201010581001900409
|View full text |Cite
|
Sign up to set email alerts
|

Falls in a Psychiatric Unit

Abstract: Our study in a psychiatric ward of a general hospital aims to identify acutely ill psychiatric patients who are at high risk of falls. Patient falls were identified by data collectors after they were reported by hospital staff into the Fall Reporting Risk Management System (RMS). From 2007 to 2009, there were a total of 26 patients who fell in the psychiatric ward. Falls are likely to occur while the patient is ambulating beside the bed and is unlikely to be elimination-related. Slipping or tripping was the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Besides the side effects of medication, it is likely that the psychiatric diagnosis could also result in changes of mental status leading to increasing risk of falls. This is supported in another cross‐sectional study which identified older patients with mood disorders, and younger female patients with eating disorders and not on psychotropic medications were at risk of falling (Meng et al, 2010). Moreover, both groups were also reported to be alert and orientated, and with no muscular weakness.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Besides the side effects of medication, it is likely that the psychiatric diagnosis could also result in changes of mental status leading to increasing risk of falls. This is supported in another cross‐sectional study which identified older patients with mood disorders, and younger female patients with eating disorders and not on psychotropic medications were at risk of falling (Meng et al, 2010). Moreover, both groups were also reported to be alert and orientated, and with no muscular weakness.…”
Section: Discussionmentioning
confidence: 77%
“…Further, most falls took place while the patients were walking next to the bed but these did not result in severe injuries. Mostly, the patients were alert alert, oriented, and did not exhibit muscle weakness or a prior history of falls (Meng et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation